Leveraging Youth Engagement for Mental Health Decision-Making: Lessons for Workplace Health Promotion - Stringer, Jillian; Levac, Braeden; Greer, Katelyn; Smith, Stacie; Musa, Ervis; Comeau, Briana; Osman, Sam; Johnston, Kylie; Wong, Chelsea; Chopra, Reeti; Moradkhan, Fatemeh Matin (The Canadian Journal of Action Research, 2026)
This study explores the use and organizational impact of youth engagement practices within the public Youth Mental Health and Substance Use (YMHSU) sector. This study used a youth participatory action approach, co-led and co-authored by youth researchers, to interview representatives from seven Canadian YMHSU organizations through a social constructivist lens. Transcripts were analyzed using thematic analysis and synthesized by a national youth research team. Respondents articulated that meaningful youth engagement necessitates a foundational organizational commitment, the creation of safe and inclusive spaces, the nurturing of authentic relationships, and the provision of diverse opportunities tailored to resonate with the unique needs and perspectives of youth participants. These practices supported organizational innovation, recruitment, retention, goal attainment, and sustainability. Participants shared success stories that illustrated the transformative impact of engagement practices within their organizations. This study highlights the organizational benefits and critical success factors for effective youth engagement in mental health decision-making and leverages a youth-centered approach to do so. Youth engagement strategies have the potential to yield significant benefits when implemented with a focus on safety and equity. We propose these strategies can and should be leveraged widely across fields to support organizational effectiveness, workplace mental health promotion, and service delivery.